EARLY HEAD START FAMILIES' EXPERIENCES WITH STRESS: UNDERSTANDING VARIATIONS WITHIN A HIGH‐RISK, LOW‐INCOME SAMPLE. Issue 5 (26th August 2017) - Hustedt, Jason T.; Vu, Jennifer A.; Bargreen, Kaitlin N.; Hallam, Rena A.; Han, Myae
ABSTRACT: The federal Early Head Start program provides a relevant context to examine families' experiences with stress since participants qualify on the basis of poverty and risk. Building on previous research that has shown variations in demographic and economic risks even among qualifying families, we examined possible variations in families' perceptions of stress. Family, parent, and child data were collected to measure stressors and risk across a variety of domains in families' everyday lives, primarily from self‐report measures, but also including assay results from child cortisol samples. A cluster analysis was employed to examine potential differences among groups of Early Head Start families. Results showed that there were three distinct subgroups of families, with some families perceiving that they experienced very high levels of stress while others perceived much lower levels of stress despite also experiencing poverty and heightened risk. These findings have important implications in that they provide an initial step toward distinguishing differences in low‐income families' experiences with stress, thereby informing interventions focused on promoting responsive caregiving as a possible mechanism to buffer the effects of family and social stressors on young children.